THE ROLE OF ORGANIZATIONAL CULTURE AND JOB SATISFACTION IN MEDIATING THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Arifiani, Ratya Shafira; Sudiro, Achmad; Indrawati, Nur Khusniyah (Jurnal Aplikasi Manajemen, 2020)
This research aimed to analyze the direct and indirect effects of transformational leadership and organizational citizenship behavior. The additions of mediating variables were organizational culture and job satisfaction. The population in this research was all nurses at the University of Muhammadiyah Malang Hospital. The sampling technique used proportional random sampling with a total sample of 109 respondents. The data analysis used path analysis. The results showed that transformational leadership had no effects on Organizational Citizenship Behavior, organizational culture on Organizational citizenship behavior is significant, transformational leadership had an influence on organizational culture, organizational culture mediated the influence of transformational leadership on Organizational Citizenship Behavior, transformational leadership affected job satisfaction, job satisfaction had no effects on Organizational Citizenship Behavior, and job satisfaction did not mediate the influence of transformational leadership on Organizational Citizenship Behavior. Therefore, future researchers can conduct research related to transformational leadership on Organizational Citizenship Behavior and can develop a research model by adding other variables such as Islamic work ethics and work discipline.